Spectrophotometric detection of arsenic using flow-injection hydride generation following sorbent extraction preconcentration - Neto, JAG; Montes, R.; Cardoso, Arnaldo Alves [UNESP] (Elsevier B.V., 1999)
An automated system with a C-18 bonded silica gel packed minicolumn is proposed for spectrophotometric detection of arsenic using flow-injection hydride generation following sorbent extraction preconcentration. Complexes formed between arsenic(III) and ammonium diethyl dithiophosphate (ADDP) are retained on a C-18 sorbent. The eluted As-DDP complexes are merged with a 1.5% (w/v) NaBH4 and the resulting solution is thereafter injected into the hydride generator/gas-liquid separator. The arsine generated is carried out by a stream of N-2 and trapped in an alkaline iodine solution in which the analyte is determined by the arsenomolybdenum blue method. With preconcentration time of 120 s, calibration in the 5.00-50.0 mu g As l(-1) range and sampling rate of about 20 samples h(-1) are achieved, corresponding to 36 mg ADDP plus 36 mg ammonium heptamolybdate plus 7 mg hydrazine sulfate plus 0.7 mg stannous chloride and about 7 mi sample consumed per determination. The detection limit is 0.06 mu g l(-1) and the relative standard deviation (n = 12) for a typical 17.0 mu g As l(-1) sample is ca. 6%. The accuracy was checked for arsenic determination in plant materials from the NIST (1572 citrus leaves; 1573 tomato leaves) and the results were in agreement with the certified values at 95% confidence level. Good recoveries (94-104%) of spiked tap waters, sugars and synthetic mixtures of trivalent and pentavalent arsenic were also found. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: spectrophotometry; hydride generation; flow-injection analysis; ammonium diethyl dithiophosphate; arsenic